How Do Profitability, Risk, and Growth Expectations Affect Market Valuation? An Analysis of P/E and P/B Ratios - Samuel Tarigan; Maradona NC Tambunan (Riviera Publishing, 2026)
The Indonesian capital market has developed rapidly in recent years, yet many retail investors still make investment decisions based on trends or unverified information rather than fundamental analysis. This study analyzes how various financial variables affect stock value using P/E and P/BV ratios as measures. The variables studied include DPR, ROE, growth potential, and market risk (Beta) in a sample of 183 Indonesian companies listed on the stock exchange and distributing dividends for the 2023 fiscal year. Audited financial statements were used as the main data source, and multiple linear regression analysis was used to analyze the data. Statistical analysis shows that DPR has a significant and positive effect on the P/E and P/BV ratios. Meanwhile, ROE has a significant but negative effect on the P/E ratio and a significant and positive effect on the P/BV ratio. Furthermore, Beta has a significant and negative effect on the P/E and P/BV ratios, while growth potential has no effect on either measure. These results provide valuable insights for investors and management regarding how various financial variables affect stock valuations influenced by the Indonesian capital market. These findings provide valuable insights for investors and management regarding how various financial variables affect stock valuations in the Indonesian capital market. For future research, it is suggested to use forward-looking growth measures such as analyst earnings forecasts or the Gordon Growth Model, as well as to explore macroeconomic variables and industry sectors to gain a more comprehensive understanding of the factors influencing stock valuation.